PERTUMBUHAN DAN PERKEMBANGAN ABK - Puriana Situmorang; Annisa Sari Harahap; Rahmah Yasrah Dalimunthe; Sri Wahyuni (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this study is to find out the theory of student development. This type of research is library research. This research makes Library materials as its main data source. Impaired children in society have many terms, teachers generally call children unruly, and are called bad children. Psychologists call children emotionally disturbed or children inhibited emotions. There are many other terms that are often used, generally hinting at the similarity of meaning, namely